Strategi Pengembangan Komoditas Sagu di Kabupaten Konawe - La Ode Ilmin Yuntafau; Haji Saediman; Muhammad Arief Dirgantoro (Universitas Halu Oleo, 2022)
Sago (Metroxylon sp.) is a tropical wet palm plant, which has a strong adaptation to grow on marginal lands. Sago is one of the potential food commodities as a source of carbohydrates owned by Indonesia. The objectives of this study were: identify the factors that are the strengths, weaknesses, opportunities and threats of sago commodity development; and determine the strategy for sago commodity development. This research was conducted in the Districts of Bondoala, Besulutu, Sampara and Kapoiala, Konawe Regency. The respondents of this study were the relevant government agencies staf in Konawe Regency and in Southeast Sulawesi Province, researchers from the Southeast Sulawesi AIAT and Development Agency and lecturers at the UHO Faculty of Agriculture, and collectors and inter-island traders. The analytical method used is SWOT-AHP (Analytical Hierarchy Process) analysis. The results of the study revealed that the strategy for developing sago commodities, which had the highest priority value or the most important ones, were the development of human resources for sago farmers and small and medium industries (IKM); strengthening coordination and synchronization of policies between institutions in the development of sago; policy on the expansion and protection of sago land; optimization of market share; diversification of sago products; increasing the competitiveness of processed sago products through the adoption of production technology; modernization of equipment and processing of sago to strengthen added value; and forming partnerships both market and capital.Keywords: development strategy; SWOT-AHP; sago